A Analysis of The Capture Result of Flat Panel Detector Design with Arduino-Based BPW34 Photodiode Sensor against mA and kV Settings - Muhammad Rois Amin; Muhammad Fajar Wahyudi; Muhammad Ridha Makruf; Tri Bowo Indrato; Andjar Pudji; Satheeshkumar Palanisamy (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
The exposure factor is the factor that determines the intensity and quality of X-rays received by the patient. Exposure factors that can be controlled are: tube voltage (kV), tube current (mA), irradiation time (second), and distance of the X-ray tube to the film (FFD). The purpose of this study was to capture X-rays at a relatively affordable manufacturing price and to obtain a difference in value from the detector's catch between dark and light by utilizing the response of the BPW34 photodiode sensor. The contribution of this study is that the system can display grayscale and numerical on an 8x8 pixel matrix using the Matrix Laboratory (MATLAB) Application. This study was able to convert images taken from analog data after taking measurements on X-rays. The measurements are carried out by 2 methods, there are range used was 32-63mA, with a tube voltage of 50 kV at an irradiation duration of 1 second and 50 - 70 kV, with a tube current of 40 mA and an irradiation duration of 1 second. From the measurement results, it shows that the Flat Panel Detector Design Tool after being compared with the Philips brand DR is able to respond to differences in dose and object thickness. The results of this study indicate that this tool can be used to capture X-rays so that the degree of blackness of the film can be known.